2015
DOI: 10.1007/s00261-015-0586-6
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality approach for imaging of non-traumatic acute abdominal emergencies

Abstract: "Acute abdomen" includes spectrum of medical and surgical conditions ranging from a less severe to life-threatening conditions in a patient presenting with severe abdominal pain that develops over a period of hours. Accurate and rapid diagnosis of these conditions helps in reducing related complications. Clinical assessment is often difficult due to availability of over-the-counter analgesics, leading to less specific physical findings. The key clinical decision is to determine whether surgical intervention is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 78 publications
3
14
1
9
Order By: Relevance
“…The diagnosis was confirmed by obtaining operative data in 2 cases (100%). In contrast to Gangadhar et al, who stated that intestinal ischemia is the second most common cause of bowel-related non-traumatic abdominal pain coming in order of frequency after IBD [15]. In our study, only 2 cases (4%) of the total population were diagnosed as having bowel ischemia.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The diagnosis was confirmed by obtaining operative data in 2 cases (100%). In contrast to Gangadhar et al, who stated that intestinal ischemia is the second most common cause of bowel-related non-traumatic abdominal pain coming in order of frequency after IBD [15]. In our study, only 2 cases (4%) of the total population were diagnosed as having bowel ischemia.…”
Section: Discussioncontrasting
confidence: 93%
“…Proximal dilatation involving the stomach and the second part of the duodenum is noted. This is agreeing with Gangadhar et al who stated that acute aorto-mesenteric angle of less than 25°and attenuated aorto-mesenteric distance of less than 10 mm at the level of the third part of the duodenum are the main diagnostic criteria of SMA syndrome along with proximal bowel dilatation [15].…”
Section: Discussionsupporting
confidence: 91%
“…Of the total, 108 (12.9%) CT scans with normal results were found and 231 (27.7%) were considered unspecific for AAP, which is lower than the frequency reported in the literature 14 The analysis was directed to diagnoses of NSAP, OU and AP, which together account for more than 70% of the final diagnoses. As broadly reported in other studies, the CT showed a high degree of accuracy [1][2][3][4][5] , with a moderate correlation between clinical, post-CT and final diagnoses for NSAP and OU and excellent for AP. However, patients with a final and tomographic diagnosis of NSAP, OU and AP already showed clinical suspicion in more than 50% of the cases, reaching more than 90% for patients with AP, and thus, can be considered clinically unnecessary.…”
Section: Discussionsupporting
confidence: 81%
“…However, if these initial investigations do not provide a diagnosis, it is clear that some patients (e.g. retroperitoneal perforation, or those unable to stand for an erect abdominal radiograph because of pain) will require more advanced imaging, such as CT, ultrasound, or MRI …”
Section: Discussionmentioning
confidence: 99%
“…retroperitoneal perforation, or those unable to stand for an erect abdominal radiograph because of pain) will require more advanced imaging, such as CT, ultrasound, or MRI. 20,21…”
Section: Discussionmentioning
confidence: 99%